The accuracy of cell‐free fetal DNA‐based non‐invasive prenatal testing in singleton pregnancies: a systematic review and bivariate meta‐analysis. (31st May 2016) - Mackie, FL; Hemming, K; Allen, S; Morris, RK; Kilby, MD
Abstract : Background: Cell‐free fetal DNA (cffDNA) non‐invasive prenatal testing (NIPT) is rapidly expanding, and is being introduced at varying rates depending on country and condition. Objectives: Determine accuracy of cffDNA‐based NIPT for all conditions. Evaluate influence of other factors on test performance. Search strategy: Medline, Embase, CINAHL, Cochrane Library, from 1997 to April 2015. Selection criteria: Cohort studies reporting cffDNA‐based NIPT performance in singleton pregnancies. Data collection and analysis: Bivariate or univariate meta‐analysis and subgroup analysis performed to explore influence of test type and population risk. Main results: A total of 117 studies were included that analysed 18 conditions. Bivariate meta‐analysis demonstrated sensitivities and specificities, respectively, for: fetal sex, 0.989 (95% CI 0.980–0.994) and 0.996 (95% CI 0.989–0.998), 11 179 tests; rhesus D, 0.993 (95% CI 0.982–0.997) and 0.984 (95% CI 0.964–0.993), 10 290 tests; trisomy 21, 0.994 (95% CI 0.983–0.998) and 0.999 (95% CI 0.999–1.000), 148 344 tests; trisomy 18, 0.977 (95% CI 0.952–0.989) and 0.999 (95% CI 0.998–1.000), 146 940 tests; monosomy X, 0.929 (95% CI 0.741–0.984) and 0.999 (95% CI 0.995–0.999), 6712 tests. Trisomy 13 was analysed by univariate meta‐analysis, with a summary sensitivity of 0.906 (95% CI 0.823–0.958) and specificity of 1.00 (95% CI 0.999–0.100), from 134 691 tests. False and inconclusive results were poorly reported across all conditions. Although the test type affected both sensitivity and specificity, there was no evidence that population risk had any effect. Conclusion: Performance of cffDNA‐based NIPT is affected by condition under investigation. For fetal sex and rhesus D status, NIPT can be considered diagnostic. For trisomy 21, 18, and 13, the lower sensitivity, specificity, and disease prevalence, combined with the biological influence of confined placental mosaicism, designates it a screening test. These factors must be considered when counselling patients and assessing the cost of introduction into routine care. Tweetable abstract: cffDNA NIPT accuracy high, can be diagnostic for fetal sex and rhesus D, but only screening test in aneuploidy. Tweetable abstract: cffDNA NIPT accuracy high, can be diagnostic for fetal sex and rhesus D, but only screening test in aneuploidy.